Non-utilization of postnatal care and its associated factors among women who gave birth in rural districts of Northern Ethiopia: A community-based mixed-method study - Getu Amsalu; Asmare Talie; Wubishet Gezimu; Abdissa Duguma (Women's Health, 2022)
Objectives: This study assessed the non-utilization of PNC services, identified factors associated with PNC non-utilization, and explored barriers to PNC utilization in the rural community. Method: A community-based mixed-cross-sectional study was conducted from 20 March to 20 April 2020 among 521 women who gave birth in the last 12 months prior to this survey. A multistage sampling and face-to-face interview techniques were used for the quantitative data collection, and a purposive sampling technique was used to select the study participants. In-depth interviews were used for the qualitative data collection. The quantitative data were entered into EpiData version 3.1 and then exported to SPSS version 25 for analysis. A binary logistic regression analysis was used to test the association between the independent and outcome variables. A p -value of <0.2 was used as the cutoff value to include variables in the multivariate analysis. Finally, a p -value of <0.05 was used to declare an independent association. The qualitative data were manually sorted, cleaned up, and labeled as themes. Every major theme was identified and enumerated, and the meaning units were cited together with the relevant participant’s socio-demographic details. Result: The non-utilization of postnatal care was found to be 75.4% in the area. Normal delivery, fewer than four antenatal care visits, inaccessibility to transportation, and poor knowledge of postnatal care were all identified as factors enhancing non-utilization of postnatal care. However, being informed about postnatal care positively influences postnatal care utilization. Poor awareness, information gaps, cultural and religious beliefs, service inaccessibility, and the unfriendly approach of healthcare workers were all explored as barriers in the qualitative study. Conclusions: The non-utilization of PNC services in this study was higher than the majority, but not all, of the previous comparable local and worldwide findings. Mode of delivery, hearing postnatal care information, the number of antenatal visits, transportation availability, and knowledge of postnatal care services were factors affecting the non-utilization of postnatal care. The clients’ poor awareness, information gaps, cultural and religious beliefs, service inaccessibility, and healthcare staff’s inauspicious approach were barriers explored. Therefore, counseling and transportation access need to be reinforced in the setting.